Obtención de un producto congelado a partir del Colossoma macropomun (gamitana) empacado al vacío - Torres Alvarado, Lizzie Fiorella (2015)
The research work was developed in order to obtain frozen fish from the species Colossoma macropomun. The raw material was obtained from the Fish Research Center of the Faculty of Biological Sciences located on the Iquitos-Nauta-Quistococha - San Juan Bautista highway. The balanced factorial design of two study factors has been applied for the species of Colossoma Macropomun (Gamitana): Factor A (type of cut) and Factor B (type of packaging). Factor A with three levels of study (whole without head, pieces or medallions and whole with head). Factor B with three levels of study (4 micron High Density Polyethylene, Bilaminar Packaging, Trilaminar Packaging). Different control methods have been carried out, which were Controls on the raw material, (Degree of freshness, pH test, Eber test, Refractive Index). Controls during the process (pH Test, Eber Test and Individual Hygiene Controls and Good Manufacturing Practices) and Controls of the Finished Product (Physicochemical Analysis, Microbiological Analysis, Sensory Analysis and Statistical Analysis of the data). In the results of the evaluation of the raw material in the Eber Reaction, they were negative and the lower values of the Refractive Index, which means that they belong to fresh fish. In the results of the Microbiological Evaluation, they gave values that do not exceed the levels allowed by MINSA, so we can say that it is a good quality product for human consumption. It was determined that the shelf life of the frozen Gamitana in its three study levels at -18 °C is 08 months.